Pengaruh Kualitas Audit,Audit Tenure,Profitabilitas,Pertumbuhan Perusahaan terhadap Opini Audit Going Concern pada Perusahaan Pertambangan Yang Terdaftar di BEI Tahun 2016-2019 - Ono Parhusip; Elfrida Fitri Hutasoit; Wenny Anggeresia Ginting (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This research was conducted to test and analyze whether the quality of audit, audit tenure, profitability, growth of the company influences the opinion of audit going concerned on mining companies listed on the Indonesia Stock Exchange for the period 2016-2019. The research method used quantitative method and research data obtained from www.IDX.co.id and research population of 47 companies, sampling is used purposive sampling techniques so that the samples in this study as many as 17 companies and this research using logistic regression test. The significance value obtained from the results of simultaneous hypothesis testing amounted to 0.007 < 0.05 that the quality of audits, audit tenure, profitability, growth of the company influenced the opinion of the audit going concerned. The significance values indicated from partial hypothesis testing were audit quality of 0.998 > 0.05, audit tenure of 0.419 > 0.05, profitability of 0.540 > 0.05, and company growth of 0.816 > 0.05. It can be seen that the quality of audits, audit tenure, profitability, and growth of the company are not partially impacted by the opinion of the audit going concerned. Keywords: Audit Quality, Audit Tenure, Profitability, Company Growth, Going Concern